Basket-work, well-being and recovery: The story from Scotland. Issue 1 (1st March 2020) - Bunn, Stephanie
AbstractThis chapter explores the relationship between craft and well-being through a close examination of the relationship between craftwork, specifically basketry, and cognition. The author argues that the exploratory, gestural and embodied skills manifest in basketry-in-action enhance creative thinking and spatial understanding of a person's environment. This enhanced understanding arises through the physical and neurological developments which grow during becoming skilful. This attribute of crafts such as basketwork to enhance cognition is equally valuable for people with memory loss, and also for those who have experience acquired bran injury or stroke. Here, new learning can both provide resonance with former skills, and also enable new neural pathways to become established, often enabling a degree of recovery to take place.